Biology of Triatoma klugi Carcavallo, Jurberg, Lent & Galvão 2001 (Heteroptera: Reduviidae) under Laboratory Conditions: Effects of Distinct Blood Sources and Susceptibility to Trypanosoma cruzi and Trypanosoma rangeli - Emmanuelle-Machado Priscilla; Koerich Leonardo B; Joukoski Daiene De Boni; Carvalho-Pinto Carlos J; Grisard Edmundo C; Steindel Mário (Memorias do Instituto Oswaldo Cruz, 2002)
The life cycle of Triatoma klugi Carcavallo, Jurberg, Lent & Galvão 2001 was compared under laboratory conditions using two groups of the F1 generation obtained from field-collected bugs. Among the 100 nymphs weekly fed on mice (Group A) or chicken (Group B), 77% of Group A and 67% of Group B reached the adult stage, and the mean time from the first nymphal stage to adult was 190.08 ± 28.31 days and 221.23 ± 40.50, respectively. The average span in days for each stage per group and the number of blood meals required for each stage were also evaluated. The overall mortality rate was 23% and 33% for Groups A and B, respectively. The mean number of eggs laid per month in a three-month period was of 56.20, 51.70 and 73.20 for Group A, and 64.50, 53.50 and 38.71 for Group B. Despite the blood source, comparative analysis revealed no statistically significant differences in the life cycle of T. klugi under laboratory conditions. Infection rates over 60% were observed for both Trypanosoma cruzi strains tested. Even revealing high infection rates of the hemolymph by T. rangeli strains, T. klugi revealed no salivary gland infections and was not able to transmit the parasite.